Development and validation of a novel informational booklet for pediatric long‐term ventilation decision support. Issue 5 (23rd December 2020) - Edwards, Jeffrey D.; Panitch, Howard B.; George, Maureen; Cirrilla, Anne‐Marie; Grunstein, Eli; Wolfe, Joanne; Nelson, Judith E.; Miller, Rachel L.
Abstract: Objectives: To provide accessible, uniform, comprehensive, and balanced information to families deciding whether to initiate long‐term ventilation (LTV) for their child, we sought to develop and validate a novel informational resource. Methods: The Ottawa Decision Support Framework was followed. Previous interviews with 44 lay and 15 professional stakeholders and published literature provided content for a booklet. Iterative versions were cognitive tested with six parents facing decisions and five pediatric intensivists. Ten parents facing decisions evaluated the booklet using the Preparation for Decision Making Scale and reported their decisional conflict, which was juxtaposed to the conflict of 21 parents who did not read it, using the Decisional Conflict Scale. Twelve home ventilation program directors evaluated the booklet's clinical sensibility and sensitivity, using a self‐designed six‐item questionnaire. Data presented using summary statistics. Results: The illustrated booklet (6th‐grade reading level) has nine topical sections on chronic respiratory failure and invasive and noninvasive LTV, including the option to forgo LTV. Ten parents who read the booklet rated it as helping "Quite a bit" or more on all items of the Preparation for Decision Making Scale and had seemingly less decisional conflict than 21 parents who did not. Twelve directors rated it highly for clinical sensibility and sensitivity. Conclusions: The LTV booklet was rigorously developed and favorably evaluated. It offers a resource to improve patient/family knowledge, supplement shared decision‐making, and reduce decisional conflict around LTV decisions. Future studies should validate it in other settings and further study its effectiveness.